2018
DOI: 10.3390/ma11060968
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of TiC0.7N0.3-HfC-WC-Ni-Mo Cermet Tool Materials

Abstract: TiC0.7N0.3-HfC-WC-Ni-Mo cermet tool materials were fabricated by hot pressing technology at 1450 °C. The effects of WC (tungsten carbide) content on the microstructure and mechanical properties of TiC0.7N0.3-HfC-WC-Ni-Mo cermet tool materials were investigated. The results showed that the TiC0.7N0.3-HfC-WC-Ni-Mo cermets were mainly composed of TiC0.7N0.3, Ni, and (Ti, Hf, W, Mo)(C, N); there were three phases: a dark phase, a gray phase, and a light gray phase. The dark phase was the undissolved TiC0.7N0.3, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Compared with the samples without WC, the K IC of the samples containing WC is improved to a certain extent. Gao et al 43 . found that since the wettability of Ni with WC was much better than that of Ni with TiCN, the relative density and comprehensive properties of the samples were improved with the increase of WC content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the samples without WC, the K IC of the samples containing WC is improved to a certain extent. Gao et al 43 . found that since the wettability of Ni with WC was much better than that of Ni with TiCN, the relative density and comprehensive properties of the samples were improved with the increase of WC content.…”
Section: Resultsmentioning
confidence: 99%
“…42 Compared with the samples without WC, the K IC of the samples containing WC is improved to a certain extent. Gao et al 43 found that since the wettability of Ni with WC was much better than that of Ni with TiCN, the relative density and comprehensive properties of the samples were improved with the increase of WC content. Similarly, the addition of WC also improves the wettability of Co to HEC 6 phase and enhances the intergranular interfacial bonding force, thus improving the mechanical properties of cermet.…”
Section: 33mentioning
confidence: 99%
“…Cutting experiments were performed on the i5T5 intelligent lathe under dry cutting condition. TiCN–HfC [7] (TH) and TiCN–HfC–WC [8] (THW) ceramics were obtained through the hot-pressing sintering technology; their mechanical properties and microstructures were showed in Table 1; HV, σ and K IC presented Vickers Hardness, flexural strength and fracture toughness, respectively. TH and THW tools were a cuboid with a size of 12mm × 12mm × 8 mm as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, the reinforcements such as WC, VC, TaC, NbC and Mo 2 C, and metal phase such as Ni, Co and Mo were employed in TiCN ceramic, which was aimed at improving fracture toughness [4][5][6]. In our previous research, the novel TiCN-HfC [7] and TiCN-HfC-WC [8] ceramics had been fabricated by hot-press sintering technology; they had good fracture toughness, hardness and flexural strength; however, their cutting performances and wear mechanisms have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation